The Role of Conflict Management in Enhancing the Effectiveness of Multicultural Da'wah in Indonesia - Randi Tamirano (Al-Amru: Jurnal Komunikasi dan Dakwah Islam, 2026)
In the context of cultural, religious, and ethnic diversity in Indonesia, multicultural da'wah plays an important role in building social harmony and strengthening community cohesion. However, this diversity also poses challenges in the form of conflicts that can hinder the effectiveness of the dissemination of religious messages. This study aims to examine the role of conflict management in increasing the effectiveness of multicultural da'wah in Indonesia through a mixed methods approach, which combines qualitative and quantitative analysis. Data was collected from 150 respondents, including dai, religious leaders, and da'wah institution managers, through in-depth interviews, field observations, and structured questionnaires. The results of the study showed a significant positive relationship between adaptive and collaborative conflict management strategies and the effectiveness of multicultural da'wah. Strategies such as inclusive dialogue, strengthening tolerance, and the use of cultural and religious mediators have proven effective in reducing conflict and promoting social harmony. These findings support the development of contextual local values-based conflict management models, which can serve as a guide for da'wah practitioners and managers in designing inclusive and effective strategies in Indonesia's multicultural society.